The effects of statins in patients with advanced-stage cancers - a systematic review and meta-analysis - Zhou, Qiang; Jiao, Zhihua; Liu, Yuxi; Devreotes, Peter N.; Zhang, Zhenyu (Frontiers in Oncology, 2023)
Statin therapy has been shown to reduce mortality in a wide range of cancer types and overall stages. Still, there is uncertainty about its efficacy in increasing survival among advanced cancer patients. We conducted a meta-analysis with data from all studies that compared the hazard ratio of overall survival, cancer-specific survival, and progression-free survival in patients with advanced-stage cancer who receive statin therapy. Studies were selected from the PubMed, Embase, and Web of Science databases from their inception to December 31, 2022. Cancer types are limited to those rarely screened during the annual examination and more likely to develop into advanced stages, such as lung, pancreatic and ovarian cancers. This resulted in 27 studies eligible for meta-analysis. Statin therapy was associated with a 26% decreased risk of overall survival (HR, 0.74; 95% CI, 0.67, 0.81), 26% decreased risk of cancerspecific survival (HR, 0.74; 95% CI, 0.61-0.88), and 24% decreased risk of progression-free survival (HR, 0.76; 95% CI, 0.65-0.87) for advanced-stage cancer patients. The associations were not attenuated or reinforced by study design, study regions, cancer types, or other medical care. Concomitant use of other anticancer medications did not result in confounding effects. Statin therapy produces significant benefits on overall survival and cancer-specific survival. Although the benefits might be lower than the approved immunotherapy medications, its cost-effectiveness could lead to dramatic health consequences. Concomitant use of statin drugs as cancer treatments is highly recommended in future clinical trials.